PROBLEM-BASED APPROACH IN TEACHING MATHEMATICS AT ECONOMIC UNIVERSITIES - Abduraxmanova Yulduz Muxtarxodjaevna (Bright Mind Publishing, 2025)
This article explores the implementation of a problem-based approach in teaching mathematics at economic universities, with a particular focus on the educational context of Uzbekistan. As the demand for highly skilled and analytically capable economic specialists grows, traditional methods of teaching mathematics often fall short in equipping students with practical problem-solving abilities. The article examines the core principles of problem-based learning (PBL) and its relevance in developing critical thinking, analytical reasoning, and applied knowledge among students in economic programs. It also highlights the challenges of integrating PBL into mathematics curricula and offers insights into pedagogical innovations, interdisciplinary alignment, and curriculum design strategies that can enhance the effectiveness of mathematical education in economic disciplines. The study is supported by a review of national and international best practices and emphasizes the importance of adapting teaching methodologies to meet the needs of the modern economic labor market.
Keywords: Problem-based learning, mathematics education, economic universities, analytical thinking, teaching methodology, curriculum development, higher education, Uzbekistan, interdisciplinary approach, applied mathematics.